O Papel da Tributação nas Teorias de Desenvolvimento e Inflação de Roberto Campos e Octavio Bulhões: Pré 1964 - Godoy Junior, José Eduardo Pimentel de (2006)
The present text was conducted in order to construct a panel of Roberto Campos and Octavio Bulhões s thoughts concerning issues related to taxation, development and inflation in the period before 1964. The bibliography used consists essentially in books, magazines and newspapers articles written by Campos and Bulhões between 1950 and 1964 - year that the authors have assumed the command of the economy and started to implement the PAEG and the Tributary Reform of 1966. Initially, the national debate and the authors concepts of development and inflation important backgrounds understanding of their ideas on taxation - will be analyzed. Afterwards, their tributary ideas will be examined in order to verify their role in their development and inflation s projects. This analysis show that taxation had a double role: first, to stimulate development by conducting resources to encourage strategic sectors; and second, to keep inflation under control by reducing public deficit, aggregate demand and the impact on prices from instability between supply and demand